The Role of Lecturer Teaching Strategies and Learning Environments in Shaping Motivation Among Indigenous Students in Higher Education - Yan Dirk Wabiser; Febi adriana Mutiara sogalrey; Putri Ellen Gracia Risamasu; Arni Wihilmina Depondoye (AL-ISHLAH: Jurnal Pendidikan, 2025)
Higher education is expected not only to develop academic competence but also to foster students’ motivation and engagement, particularly among Indigenous learners who often face cultural and systemic barriers. This study examines how lecturers’ teaching strategies influence the learning motivation of Indigenous Papuan students, with learning styles and learning environments as potential mediators. A quantitative cross-sectional survey was conducted among 129 Indigenous students from the Faculty of Teacher Training and Education at Cenderawasih University. Data were collected using a validated questionnaire measuring teaching strategies, learning styles, learning environments, and student motivation. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to analyze the measurement and structural models. Findings revealed that lecturer teaching strategies had a significant direct impact on student motivation (β = 0.574, p 0.001) and learning environment (β = 0.680, p 0.001). The learning environment significantly mediated the relationship between teaching strategies and motivation, whereas learning styles showed no significant direct or mediating effect. The results emphasize that culturally responsive and well-structured teaching strategies, supported by an inclusive learning environment, play a crucial role in enhancing Indigenous students’ motivation. In contrast, individual learning styles had minimal influence, highlighting a shift away from traditional assumptions about learning preferences. Higher education institutions should prioritize adaptive teaching practices and culturally relevant learning environments to support the motivation and academic success of Indigenous learners.